The History of the Administrative Judiciary in Jordan from (1951 AD to 2022 AD) - Fraihat, Eman; Fraihat, Bassmah Ozbi; Abu Issa, Hamza; Qaddouri, Hussein Latif (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aimed at tracing the history of the administrative judiciary in Jordan and its development from 1951 to 2022 AD, which is concerned with looking into disputes of an administrative nature in which the public administration is a party as a public authority. Methods: The study used the historical and analytical methods to reach the facts and knowledge related to the study of the emergence and development of the administrative judiciary, the formation and convening of administrative courts, and then the conditions for appointment, their terms of reference, and challenging their rulings. Result: The Jordanian judiciary has adopted the unified judicial system, that is, making the ordinary courts jurisdiction over civil or administrative disputes, and the existence of a single state law to which everyone is subject, whether rulers or ruled. The issuance of the temporary High Court of Justice Law No. (11) In 1989 AD, the law established the turning point into the dual justice system, i.e. specializing in a certain type of cases related to administrative issues, noting that the administrative judicial development is a clear evidence of political, economic and social development Conclusions: It is necessary to expand the jurisdiction of the administrative judiciary by granting the administrative judiciary in Jordan the general jurisdiction to consider all administrative disputes.